A Neoclassical Growth Model with a Cyclical Number of Employees - Dykas, Paweł (Studia Oeconomica Posnaniensia, 2018)
The aim of the present study is an attempt to extend the neoclassical model of economic growth of Solow by repealing the assumption of fixed employees ratio and introducing an employment function dependent cyclical on the time. In the empirical analysis the author conducted a calibration of parameters used by the research model. Based on panel data for Polish employees between 2002-2015 the parameter (α ) (production flexibility in relation to capital) was estimated at 0.354. That value was adapted to a further numerical analysis. When conducting numerical analysis the impact of different investment rates (15%, 20% and 25%) and periods of cyclical fluctuations. A numerical analysis for the economy of Poland was made for a thirty five time series.